Determinants Of Under-Nutrition Among Under Five Children in The Urban Slum of Ahmedabad, India - Kachhawala, Fatema; Patel, Vaibhavi; Puwar, Bhavna (National Journal of Community Medicine, 2023)
Background: Optimal infant and young child feeding practices (IYCF) are effective public health intervention to enhance child survival, nutrition and development. There is also documented evidence regarding the protective effect of optimal IYCF practices against diarrhoea and ARTI. The objective is to assess knowledge and practices regarding IYCF among study participants & to explore the association of feeding practices of mothers with the morbidities (infections) in their children. Methodology: The present study was a hospital based cross-sectional study, carried out during September 2019 to March 2021. A total of 380 mothers of children less than two years attending OPD of Institute of child health, Nirmal hospital private limited, a tertiary care multi-specialty hospital was interviewed using pre-designed and pretested questionnaire. Results: Feeding practices during early days of life to be reasonably good among study participants with almost 2/3rd of the study participants practicing them. Mean number of morbidity episodes requiring consultation were significantly lower in the children whose mothers practiced optimal IYCF practices. Conclusion: Poor feeding practices in children had significant association with morbidity episodes of diarrhoea and ARTI in children.